2003
DOI: 10.2108/zsj.20.1109
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Reduces Plasma Leptin- and Ghrelin-Immunoreactive Peptide Concentrations of the Burbot (Lota lota) at 2°C But Not at 10°C

Abstract: The effects of fasting at two water temperatures (2 and 10 degrees C) on plasma leptin- and ghrelin-immunoreactive peptide concentrations and energy metabolism were investigated in the burbot (Lota lota), a freshwater gadoid, which lives in cold waters and tolerates long periods of fasting. Burbot were assigned to fed and fasted groups at 2 and 10 degrees C. Leptin- and ghrelin-immunoreactive peptides were identified in burbot plasma. Fasting at 2 degrees C reduced the plasma leptin- and ghrelin-immunoreactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 33 publications
(38 reference statements)
3
30
1
Order By: Relevance
“…In particular, fasting reduces leptin levels in plasma, adipose tissue and stomach, while overfeeding is accompanied by increased leptin concentrations in mammals (Ahima & Osei 2004). In fish, plasma leptin immunoreactive peptide was also reduced by 2 weeks fasting in green sunfish (Johnson et al 2000) and burbot (Nieminen et al 2003). Moreover, a positive correlation between blood leptin concentration and adiposity has been found in bluegill and white crappie (Johnson et al 2000).…”
Section: Introductionmentioning
confidence: 98%
“…In particular, fasting reduces leptin levels in plasma, adipose tissue and stomach, while overfeeding is accompanied by increased leptin concentrations in mammals (Ahima & Osei 2004). In fish, plasma leptin immunoreactive peptide was also reduced by 2 weeks fasting in green sunfish (Johnson et al 2000) and burbot (Nieminen et al 2003). Moreover, a positive correlation between blood leptin concentration and adiposity has been found in bluegill and white crappie (Johnson et al 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Only recently a fish leptin gene was identified (Kurokawa et al, 2005) and leptin-like immunoreactivity was found in the blood, brain, heart, liver, gut, and plasma of fish (Bosi et al, 2004;Ferrando et al, 2009;Huising et al, 2006;Johnson et al, 2000;Kurokawa et al, 2005;Muruzá bal et al, 2002;Mustonen et al, 2002;Nieminen et al, 2003) and in salmon adipocytes (Vegusdal et al, 2003). Several leptin roles were suggested in fish (Peyon et al, 2001;Volkoff et al, 2003;Weil et al, 2003), but its involvement in food intake and body weight is still controversial due to support by various authors (De Pedro et al, 2006;Ferrando et al, 2009;Volkoff et al, 2003) and denied by others (Baker et al, 2000;Silverstein and Plisetskaya, 2000;Londraville and Duvall, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Volkoff and Peter (2001) showed that the central injection of leptin increased CART mRNA in the optic tectum, hypothalamus, and olfactory bulbs, and suggested that CART might serve as a leptinregulated satiety factor in goldfish. Plasma leptin was reduced in green sunfish and burbot following fasting for 2 weeks (Johnson et al, 2000;Nieminen et al, 2003).…”
mentioning
confidence: 99%